2006
DOI: 10.1039/b511339c
|View full text |Cite
|
Sign up to set email alerts
|

To stir or not to stir: formation of hierarchical superstructures of molecularly ordered ethylene-bridged periodic mesoporous organosilicas

Abstract: The effect of stirring during the synthesis of mesoporous organosilica materials prepared via surfactant (cetyltrimethylammonium bromide, CTAB) mediated assembly of distilled 1,2bis(triethoxysilyl)ethylene (BTEE) under basic conditions has been probed. A variety of hierarchical superstructures of periodic mesoporous organosilicas that contain molecularly ordered ethylene groups were obtained by simply varying the extent of stirring (i.e., agitation of the synthesis gels). Under static conditions, large (>10 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…This phenomenon means that the organic groups in all the samples of the PMOs are stable up to 250 8C. [40,41] A second weight loss is observed in the MI10 and MI30 samples near 500 8C (see Figure 7 b and Figure S3 in the Supporting Information), which is associated with thermal degradation of the cross-linked organosilicate framework in these materials. A gradual increase in the weight loss in the range 250-600 8C was proportional to the amount of the organic bridges incorporated into the hybrid materials (Figure 7 a).…”
Section: Introductionmentioning
confidence: 87%
“…This phenomenon means that the organic groups in all the samples of the PMOs are stable up to 250 8C. [40,41] A second weight loss is observed in the MI10 and MI30 samples near 500 8C (see Figure 7 b and Figure S3 in the Supporting Information), which is associated with thermal degradation of the cross-linked organosilicate framework in these materials. A gradual increase in the weight loss in the range 250-600 8C was proportional to the amount of the organic bridges incorporated into the hybrid materials (Figure 7 a).…”
Section: Introductionmentioning
confidence: 87%
“…Interestingly, other groups have also recently demonstrated that stirring in the reaction process also has a dramatic effect on the morphology of mesoporous silica particles. For example, Xia and Mokaya 19 have shown that during the surfactant-mediated synthesis of mesoporous organosilica materials, monodispersed particles of y10 mm in diameter are obtained as the predominant particle morphology if the reaction is carried out under static conditions. In contrast, fast stirring conditions generate spongy flower-like particles that extend for up to 160 mm.…”
Section: Dan LImentioning
confidence: 99%
“…The addition of bromine is already elaborately described by different research groups such as Stein et al, 22 Ozin et al, 70 Sayari et al, 73 Mokaya et al, [79][80][81] Yoshitake et al 212 and Van Der Voort et al 213 The reaction is very straightforward and easy to perform with gaseous bromine or bromine dissolved in a chlorinated solvent. Bromination of the ethenylene bond of the PMO material slightly decreases the specific surface area, pore volume and pore diameter because of the modification of the pore walls.…”
Section: Bromination Of the Double Bond -Nucleophilic Substitutionmentioning
confidence: 93%
“…80 Different types of particles were also prepared depending on the agitation conditions. 81 Tatsumi et al 82 synthesized hexagonal (P6mm) ethenyleneand phenylene-bridged PMOs with helical mesostructures from BTEENE and BTEB, respectively, in the presence of the cationic fluorinated surfactant CF 3 (CF 2 ) 3 SO 2 NH(CH 2 ) 3 N + (CH 3 ) 3 I À (FC-4911) and CTAB as templates. A TEM image of the phenylene-bridged PMO with helical channels is shown in Fig.…”
Section: Ethenylene-bridged Pmos (''Ethene-pmos'')mentioning
confidence: 99%